2015
DOI: 10.1016/j.canep.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer incidence around the Belgian nuclear sites: Surrogate exposure modelling

Abstract: The re-analyses refute an association with the nuclear facilities for the site of Mol-Dessel. For the site of Fleurus, one of Europe's major production sites of radio-iodines, the results were less conclusive and further research suggests itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The results of this ecological study, performed at the level of the communes (municipalities), showed no higher incidence of thyroid cancer around the two Belgian nuclear power plants. For the two nuclear sites with research and industrial activities, a slightly higher incidence of thyroid cancer was observed compared to the regional average …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results of this ecological study, performed at the level of the communes (municipalities), showed no higher incidence of thyroid cancer around the two Belgian nuclear power plants. For the two nuclear sites with research and industrial activities, a slightly higher incidence of thyroid cancer was observed compared to the regional average …”
Section: Introductionmentioning
confidence: 82%
“…For the two nuclear sites with research and industrial activities, a slightly higher incidence of thyroid cancer was observed compared to the regional average. [15][16][17][18] The present study is the follow-up thereof and follows the recommendation to make data available at smaller geographical level. The present study was performed at the level of the statistical sectors, a subdivision of commune.…”
Section: Introductionmentioning
confidence: 99%
“…Even the elevated rate of well-differentiated thyroid cancer around the nuclear plants is debated. 123,124 The influence of radiation has also been recognized when the exposure occurs in children. Case-control studies have shown a 2-fold increase in incidence when children had a history of exposure to dental X-rays.…”
Section: Radiationmentioning
confidence: 99%
“…Nonetheless, the evidence of effects in areas far away from the accident, under the path of the “radioactive cloud” is weak. Even the elevated rate of well‐differentiated thyroid cancer around the nuclear plants is debated …”
Section: Introductionmentioning
confidence: 99%
“…However, they allow to build complex high non-linear models [21][22][23][24] which it is very difficult to achieve with RSM or too complex with NN. They are then found to be a valuable tool to support a wide scope of activities in modern engineering design such as chemical and materials engineering [25,26], and other fields such as agriculture and ecology [27,28], medicine [29][30][31] and economy [32].…”
Section: Introductionmentioning
confidence: 99%